End of modernity, twilight of art. Gianni Vattimo and his philosophical paths - Górski, Jakub (Hybris, 2013)
This essay is an introduction to Vattimo’s book “The end of modernity” — the collection of thesis about the relation between modernity and post-modernity discourses. Aim of that essay is to put that relation in a context of reflection over a crucial revision about the cultural values status in late modernity. Nowadays, as Vattimo claims, “Twilight of art” comes closer asymptotical to metaphysical discourse and communication process in technological-determined world. Therefore, “the end” of modernity, or so-called “postmodernism” is a spatiotemporal, limitless, in a state of flux, boundless communication structure between peoples, values, tradition and progress, structure that makes a necessity from idea of consensus.